Clinical efficacy of pterygium surgery technique involving use of high frequency welding of biological tissues for fixing free limbal conjunctival autograft - V.Ia. Usov; E.V. Maltsev; N.I. Krytsun (Ukrainian Society of Ophthalmologists, 2015)
Background: It is important to reduce the rate of early complications following pterygium surgery. Purpose: To determine whether the use of high-frequency welding of biological tissues (HFWBS) for fixing a free limbal conjunctival autograft (LCAG) improves the efficacy of surgical treatment of pterygium. Material and Methods: We retrospectively analyzed data from 73 patients (73 eyes) who underwent free LCAG surgery for different stages of pterygium. Patients were divided into the HFWBS group (34 patients; 34 eyes) and the control group (39 patients; 39 eyes). The former underwent pterygium surgery involving the use of HFWBS for fixing a free LCAG with upgraded EK-300M1 apparatus and special bipolar forceps, and the latter underwent free LCAG with sutures following pterygium excision. Efficacy was assessed in terms of clinical signs (corneal reepithelialization rate, inflammatory response intensity, corneal syndrome intensity, and corneal transparency at the site of excised pterygium) postoperatively. Results: At day 5, (a) complete corneal re-epithelialization was significantly more often found in the HFWBS group (30/34 eyes; 88.2%) than in controls (20/39 eyes; 51.3%) (?2 = 13.7; р = 0.00021), (b) patients of the former group had neither the highest nor a high score of local inflammatory vascular response, whereas 3/39 (7.6%) patients of the latter group had the highest score of local inflammatory vascular response (?2 = 237; р = 0.00003), and (c) signs of corneal syndrome were found in 1/34 eyes (2.9%) of the HFWBS group vs 39/39 eyes (100%) of controls; i.e., corneal syndrome was observed 97.1% less often in the HFWBS group than in controls. At observation time points less than 3 months, restoration of corneal transparency was observed in 33/34 eyes (97.1%) of the HFWBS group vs 12/39 eyes (30.8%) of controls (р = 0.0001). Conclusion: First, in LCAG, the use of HFWBS significantly improves the efficacy of surgical treatment of pterygium. At day 3, complete corneal re-epithelialization was significantly more often found in the HFWBS group than in controls (73.5% vs 15.4%; difference, 58.1%). At day 5, this difference remained statistically significant and was 36.9%. Second, at all observation time points, low vascular response scores were found statistically significantly more often in the HFWBS group than in the controls (Pu < 0.015). Third, LCAG with HFWBS was found advantageous over LCAG with sutures in terms of corneal syndrome, since, at day 5, practically all eyes (33/34 eyes; 97.1%) of the HFWBS group were quiet, whereas all eyes (39/39 eyes; 100%) of the controls were mildly irritated (?2 = 69.1; р = 0.00001). Finally, at month 3, restoration of corneal transparency was observed in the HFWBS group 66.3% more often than in controls (?2 = 33.8; р = 0.00001), thus supporting the advantage of HFWBS in pterygium treatment with LCAG.